ANALYSIS OF SPEAKING DIFFICULTIES: A SURVEY AT BANK NTB SYARIAH BRANCH SRIWIJAYA - Imam, Syahrul; Zulandha Melani, Boniesta; Saputra, Agus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the speaking difficulties of English faced by staff at Bank NTB Syariah Branch Sriwijaya. Speaking is a crucial skill in professional settings, particularly in banking services, where effective communication with customers is essential. This research employs a quantitative and qualitative analysis to explore the speaking difficulties faced by staff and how they overcome these difficulties. Data were collected through a questionnaire and an interview. The respondents in this study are 10 customer service staff members at the Bank NTB Syariah branch in Sriwijaya. The findings reveal that the main difficulties in speaking English faced by staff at the Bank NTB Syariah Sriwijaya branch include a lack of confidence, limited vocabulary, limited knowledge of grammar, and poor pronunciation. Furthermore, staff at the Bank NTB Syariah Sriwijayabranch overcome their difficulties with English by practicing independently, watching videos and listening to English songs, and writing down new vocabulary.The results of this research are expected to provide insights into improving speaking skills in professional settings, especially in the banking sector, and to serve as a reference for future research in similar contexts.